2017
DOI: 10.1038/nature22990
|View full text |Cite
|
Sign up to set email alerts
|

RNase III nucleases from diverse kingdoms serve as antiviral effectors

Abstract: In contrast to the DNA-based viruses in prokaryotes, the emergence of eukaryotes provided the necessary compartmentalization and membranous environment for RNA viruses to flourish, creating the need for an RNA-targeting antiviral system1,2. Present day eukaryotes employ at least two main defense strategies that emerged as a result of this viral shift, namely antiviral RNA interference (RNAi) and the interferon (IFN) system2. Here, we demonstrate that Drosha and related RNase III ribonucleases from all three do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 39 publications
0
60
0
Order By: Relevance
“…To test this hypothesis, we cloned the 3′UTR of the BHRF1 protein, which encompasses these two pri-miRNAs, either from WT EBV or from the Δ123 EBV mutant in which the pri-miR-BHRF1-2 and 1-3 stem-loops have been mutationally inactivated, 3′ to the FLuc indicator gene. These two constructs, and a control “empty” FLuc vector lacking any inserted EBV sequences, were then transfected into wildtype 293T cells, as well as into a previously described 293T derivative in which both Drosha and Dicer expression had been blocked by gene editing, called RNaseIII−/− cells (Aguado et al, 2017). FLuc expression was then determined relative to a co-transfected NanoLuc control vector.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test this hypothesis, we cloned the 3′UTR of the BHRF1 protein, which encompasses these two pri-miRNAs, either from WT EBV or from the Δ123 EBV mutant in which the pri-miR-BHRF1-2 and 1-3 stem-loops have been mutationally inactivated, 3′ to the FLuc indicator gene. These two constructs, and a control “empty” FLuc vector lacking any inserted EBV sequences, were then transfected into wildtype 293T cells, as well as into a previously described 293T derivative in which both Drosha and Dicer expression had been blocked by gene editing, called RNaseIII−/− cells (Aguado et al, 2017). FLuc expression was then determined relative to a co-transfected NanoLuc control vector.…”
Section: Resultsmentioning
confidence: 99%
“…293T cells were grown in Dulbecco’s modified Eagle medium (DMEM) supplemented with 5% FBS, 50 μg/ml gentamicin, and 1x Antibiotic-Antimycotic. NoDice/ΔPKR cells (Kennedy et al, 2015) and RNaseIII−/− 293T cells (Aguado et al, 2017) were grown in DMEM supplemented with 10% FBS, 50 μg/ml gentamicin, and 1x Antibiotic-Antimycotic.. All cells were grown at 37°C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…We have experimentally analyzed two well‐known biochemical factors, RNase P and RNase III . Their basic domains are present in all three domains of life (although functional RNase III is limited to a subset of archaeal species), so that it is assumed that they were likely operating in the last universal common ancestor (LUCA) of past and current biodiversity . All our reaction assays were performed in vitro using purified factors.…”
Section: A Methods For Mrna Archaeologymentioning
confidence: 99%
“…Since DDX17 also interacts with enzymes in the canonical mRNA degradation machinery, it was proposed that Rm62/DDX17 may function as an RNA sensor of RVFV infection to facilitate (RNAi-independent) degradation [112]. Finally, an ancient antiviral role was demonstrated for Drosha, the RNase III component of the microprocessor complex that processes primary miRNA transcripts in the nucleus [120]. However, Drosha is proposed to act as an antiviral factor through direct recognition/processing of RNA stem loops, conform to its ancestral function, independently of the antiviral RNAi machinery (Dcr-2, Ago-2) or its role in primary miRNA processing, that both later evolved.…”
Section: No Identification Of Rnai Machinery Componentsmentioning
confidence: 99%
“…Furthermore, it was regularly observed that host factors in Drosophila cells were conserved in mammalian (human) cells [112][113][114][117][118][119][120]. The results of the screens with respect to the (validated) identification of both new resistance mechanisms (VRFs, "antiviral genes") as well as (often virus-specific) cellular processes that are limiting to viral infection (VSFs, "proviral genes") are summarized in Table 1.…”
Section: Identification Of Host Factors That Restrict Viral Infectionmentioning
confidence: 99%